Transcriptomic Analysis of the Effect of Pruning on Growth, Quality, and Yield of Wuyi Rock Tea - Qi Zhang; Ying Zhang; Yuhua Wang; Jishuang Zou; Shaoxiong Lin; Meihui Chen; Pengyao Miao; Xiaoli Jia; Pengyuan Cheng; Xiaomin Pang; Jianghua Ye; Haibin Wang (Plants, 2023)
Pruning is an important agronomic measure in tea plantation management. In this study, we analyzed the effect of pruning on gene expression in tea leaves from a transcriptomics perspective and verified the results of a transcriptomic analysis in terms of changes in physiological indicators of tea leaves. The results showed that pruning enhanced the gene expression of nine metabolic pathways in tea leaves, including fatty acid synthesis and carbohydrate metabolism, nitrogen metabolism, protein processing in the endoplasmic reticulum, and plant hormone signal transduction, thereby promoting the growth of tea plants and increasing tea yield. However, pruning reduced the gene expression of nine metabolic pathways, including secondary metabolites biosynthesis, flavonoid biosynthesis, phenylpropanoid biosynthesis, and sesquiterpenoid and triterpenoid biosynthesis, and lowered the content of caffeine, flavonoids, and free amino acids in tea plant leaves. In conclusion, pruning could promote the growth of tea plants and increase the yield of tea, but it was not conducive to the accumulation of some quality indicators in tea leaves, especially caffeine, flavonoids, and free amino acids, which, in turn, reduced the quality of tea. This study provides an important theoretical reference for the management of agronomic measures in tea plantations.